Pengaturan Tentang Milisi Dalam Hukum Humaniter Internasional - Mitsel Sopacua; Johanis Steny Franco Peilouw; Veriena Josepha Batseba Rehatta (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Militia, also know as savage troop groups, are groups of civilians that can function as a supplement to the regular military or as a challenger to counter military coups. The process of forming the militia occurred because of a conflict between a group and the state central government which resulted in conflict resulting in rebel groups being named militia or illegal troop groups.Purposes of the Research: To know about the arrangement of militias in armed conflict of a non-interntional nature. Methods of the Research: The research method used is normative research. This type of research has stages of scientific logic research based on the normative side. The legal materials in this research method are primary legal materials that are based on laws or laws that are said to be norms and also secondary legal materials that are guided by books. This research refers to international and non-international legal instruments.Results of the Research: The results of this study indicate that Militia arrangements are recognized as Belligerent as regulated in Article 1 of the Hague Convention IV of 1907 (Hague Regulations), Article 1 paragraph (1) of Additional Protocol II of 1977, in the 1949 Geneva Conventions and the 1977 Additional Protocol requiring organizations to protect and assist civilians who are victims of armed conflict. The responsibility for the action of the militia is the rebel command not only in times of armed conflict but also in times of peace.